2020
DOI: 10.1061/(asce)st.1943-541x.0002715
|View full text |Cite
|
Sign up to set email alerts
|

Design and Optimization of Cold-Formed Steel Sections in Bolted Moment Connections Considering Bimoment

Abstract: The load transfer mechanism in cold-formed steel (CFS) bolted moment connections is mainly through the bolt-group in the web of beam elements, which may lead to relatively large bimoment and warping deformation. While the bimoment effects can be considered in the Direct Strength Method (DSM), ignoring the bolt-group length in the conventional design process can lead to non-conservative solutions. This paper presents an alternative analytical design approach using Eurocode 3 (EC3) effective width method to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 36 publications
(44 reference statements)
0
15
0
Order By: Relevance
“…More recently, a coupled optimization framework at the element and structural levels was developed by Phan et al [36] to find the optimum solutions for the CFS portal frames. They also conducted shape optimization to improve the flexural capacity of the CFS beam members used in bolted moment connections by taking into account the bimoment effects [37].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a coupled optimization framework at the element and structural levels was developed by Phan et al [36] to find the optimum solutions for the CFS portal frames. They also conducted shape optimization to improve the flexural capacity of the CFS beam members used in bolted moment connections by taking into account the bimoment effects [37].…”
Section: Introductionmentioning
confidence: 99%
“…Numerical evaluation of racking systems currently is a typical approach to derive the optimum values of CFS sections and upright characteristics. Two famous numerical approaches including finite strip method and direct strength method were conducted along the genetic algorithm (GA) [25,26] to obtain the best possible upright columns [27][28][29][30]. In this study, various lengths and thicknesses of cold-formed uprights were modelled by ABAQUS with different reinforcement distances.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have experimentally and analytically investigated the structural performance of apex and eaves CFS connections under monotonic loads (e.g. [11][12][13][14][15][16][17][18][19][20][21]). It was concluded that the local buckling of CFS beam close to connection zone was normally identified as a dominant failure mode, while it was shown that bolt-group size can have a significant effect on the flexural strength of the connections.…”
Section: Introductionmentioning
confidence: 99%
“…Bučmys et al [24] presented an analytical approach to determine the rotational stiffness of CFS bolted moment connections based on the component method stipulated in Eurocode 3 [25]. In other relevant studies, Rinchen and Rasmussen [16] and Phan et al [19] developed design approaches for the flexural strength of bolted connections by considering the effects of bimoment. The design aspects of the CFS bolted moment connections were further explored by Mojtabaei et al [20], who attributed premature failure in the web of the cross-section to the shear lag effect.…”
Section: Introductionmentioning
confidence: 99%